Omniphilic polymeric sponges by ice templating - Chatterjee, Soumyajyoti; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2016)
Sponges that absorb a large quantity of solvent relative to their weight, independent of the solvent polarity, represent useful universal absorbents for laboratory and industrial spills. We report the preparation of macroporous polymer sponges by ice templating of polyethylenimine aqueous solutions and their cross-linking in the frozen state. The as-prepared monolith is hydrophilic and absorbs over 30 fold its weight in water. Modification of this sponge using valeroyl chloride renders it omniphilic; viz., a modified sponge absorbs over 10-fold its dry weight of either water or hexane. Modification using palmitoyl chloride that has a longer chain length results in the preparation of a hydrophobic sponge with a water contact angle around 130, which retains its oleophilicity underwater. The solvent absorbed in these sponges can be simply squeezed out, and the sponges are stable to several hundred cycles of compression. The large pore sizes of these sponges allow rapid absorption of even high viscosity solvents such as pump oil. Finally, we demonstrate that these sponges are also able to separate apolar oils that are emulsified in water using surfactants. These high porosity sponges with controllable solvophilicity represent inexpensive, high performance universal absorbents for general solvent spills.